Strain-regulated exsolution of Ru on hydrogen-storing oxide for ambient ammonia catalysis - Kim, Joonhwan; Kim, Hayoung; Son, Ji-Won; Kim, Young-Beom; Yang, Sungeun; Ji, Ho-Il (Royal Society of Chemistry, 2025)
Although the development of technologies for implementing a hydrogen-based clean energy system is progressing rapidly, significant challenges remain in hydrogen storage and transportation. Ammonia has emerged as a promising energy carrier due to its high gravimetric hydrogen density and relatively facile liquefaction properties. However, the current commercial production method, the Haber-Bosch process, requires high temperatures and pressures, resulting in substantial energy consumption and rendering it unsuitable for small-scale, renewable energy-based applications. To address these limitations, the development of catalysts capable of exhibiting high activity under milder conditions is essential. In this study, we developed a highly dispersed Ru nanocatalyst via exsolution, using a proton-conducting perovskite oxide, BaCe0.55Zr0.3Y0.15O3−δ (BCZY), as a support for efficient ammonia synthesis under atmospheric pressure. BCZY is capable of storing approximately 10 mol% hydrogen at 400 °C and offers excellent thermal stability. These attributes contribute to the suppression of hydrogen poisoning and enhance the structural integrity of the Ru catalyst. 5 mol% Ru-doped BCZY was synthesized, and the kinetics of Ru exsolution under reducing conditions were investigated via thermogravimetric analysis (TGA), enabling the determination of optimal conditions for maximizing nanoparticle formation. The structure and spatial distribution of the exsolved Ru nanoparticles were comprehensively characterized using X-ray diffraction (XRD), transmission electron microscopy with energy-dispersive X-ray spectroscopy (TEM-EDS), X-ray photoelectron spectroscopy (XPS), and extended X-ray absorption fine structure (EXAFS) analysis. The resulting catalyst exhibited outstanding activity for ammonia synthesis under atmospheric conditions, surpassing previously reported systems and demonstrating strong potential as a highly efficient catalyst for decentralized ammonia production.